Kualitas Layanan Online Berbasis Whatsapp dalam Pelayanan Administrasi Kependudukan - Elen Lian; Megandaru Widhi Kawuryan; Yudi Rusfiana (Public Service and Governance Journal, 2023)
The research focused on the quality of whatsapp-based online services in population administration services in kupang city. The purpose of this study is to explain the implementation and quality model of whatsapp-based online services in population administration services. The theory used is the theory of online service quality proposed by parasurahman with the variables of efficiency, fullfilment, system availability, privacy. The research design used qualitative research with a descriptive approach. The results showed that the implementation of quality whatsapp-based online services was seen from service efficiency, ease of access and a simple mechanism; fullfilment, a fast and free service period; system availability, the internet network support; and privacy, the end-to-end encrypted whatsapp. The obstacle is there are no regulations, infrastructure facilities are still limited, just using one smartphone for one service where the smartphone capacity is limited for document transactions. Then there is still a lack of government socialization. Therefore, the model that needs to be carried out by the population and civil registry office of kupang city is to make a regulation for the mayor of kupang. It is necessary for the government to be responsible for providing computers for whatsapp online, and conducting wider socialization to the public.